α-SNAP is expressed in mouse ovarian granulosa cells and plays a key role in folliculogenesis and female fertility - Alexis Arcos (Nature Portfolio, 2017)
Abstract The balance between ovarian folliculogenesis and follicular atresia is critical for female fertility and is strictly regulated by a complex network of neuroendocrine and intra-ovarian signals. Despite the numerous functions executed by granulosa cells (GCs) in ovarian physiology, the role of multifunctional proteins able to simultaneously coordinate/modulate several cellular pathways is unclear. Soluble N-ethylmaleimide-sensitive factor (NSF) attachment protein (α-SNAP) is a multifunctional protein that participates in SNARE-mediated membrane fusion events. In addition, it regulates cell-to-cell adhesion, AMPK signaling, autophagy and apoptosis in different cell types. In this study we examined the expression pattern of α-SNAP in ovarian tissue and the consequences of α-SNAP (M105I) mutation (hyh mutation) in folliculogenesis and female fertility. Our results showed that α-SNAP protein is highly expressed in GCs and its expression is modulated by gonadotropin stimuli. On the other hand, α-SNAP-mutant mice show a reduction in α-SNAP protein levels. Moreover, increased apoptosis of GCs and follicular atresia, reduced ovulation rate, and a dramatic decline in fertility is observed in α-SNAP-mutant females. In conclusion, α-SNAP plays a critical role in the balance between follicular development and atresia. Consequently, a reduction in its expression/function (M105I mutation) causes early depletion of ovarian follicles and female subfertility.